Risk factors for Type 2 Diabetes Mellitus in college students: association with sociodemographic variables - Adman Câmara Soares Lima; Márcio Flávio Moura Araújo; Roberto Wagner Júnior Freire de Freitas; Maria Lúcia Zanetti; Paulo César de Almeida; Marta Maria Coelho Damasceno (Universidade de São Paulo, 2014)
OBJECTIVE: identify the modifiable risk factors for type 2 diabetes mellitus in college students and associate these factors with their sociodemographic variables.METHOD: cross-sectional study, involving 702 college students from Fortaleza-CE, Brazil. Sociodemographic, anthropometric, physical exercise data and blood pressure and fasting plasma glucose levels were collected.RESULTS: the most prevalent risk factor was sedentariness, followed by overweight, central obesity, high fasting plasma glucose and arterial hypertension. A statistically significant association was found between overweight and sex (p=0.000), age (p=0.004) and marital status (p=0.012), as well as between central obesity and age (p=0.018) and marital status (p=0.007) and between high fasting plasma glucose and sex (p=0.033).CONCLUSION: distinct risk factors were present in the study population, particularly sedentariness and overweight.